David K. Pettegrew. The Isthmus of Corinth. Crossroads of the Mediterranean world - Peeters, Dean (Journal of Greek Archaeology, 2017)
David Pettegrew’s book The Isthmus of Corinth. Crossroads of the Mediterranean world is an admirable synthesis on the landscape of the Isthmus, its urban and rural habitation and the socio-economic and political development of the area from the period of first Roman involvement in the region up till the early fifth century CE. The main aim of the book is to provide a new contextualised vision of the Isthmus, reacting against the timeless, static, and in some sense simplistic, view of a natural landscape that always functioned as a prosperous node of high socio-economic connectivity in the Mediterranean.